2020
DOI: 10.1002/jcp.29796
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a four immune‐related genes signature based on an immunogenomic landscape analysis of clear cell renal cell carcinoma

Abstract: Renal clear cell carcinoma (ccRCC) is the most common type of renal cell carcinoma, which has strong immunogenicity. A comprehensive study of the role of immune‐related genes (IRGs) in ccRCC is of great significance in finding ccRCC treatment targets and improving patient prognosis. In this study, we comprehensively analyzed the expression of IRGs in ccRCC based on The Cancer Genome Atlas datasets. The mechanism of differentially expressed IRGs in ccRCC was analyzed by bioinformatics. In addition, Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 59 publications
2
17
1
Order By: Relevance
“…We inferred that the decreased proportion of resting mast cells, which re ected the enhancement of activated mast cells activities, was associated with a poor prognosis due to the protumorigenic effects of activated mast cells. In addition, a previous study showed a four immune-related genes signature based on CXCL2, SEMA3G, PDGFD, and UCN is closely associated with the prognosis of renal clear cell carcinoma (Gao et al 2020). In this study, we identi ed that TIICs proportion is closely correlated with the prognosis of renal cancer, which was diffent from the previous study.…”
Section: Different Immune Clusters Are Associated With the Prognosis contrasting
confidence: 62%
“…We inferred that the decreased proportion of resting mast cells, which re ected the enhancement of activated mast cells activities, was associated with a poor prognosis due to the protumorigenic effects of activated mast cells. In addition, a previous study showed a four immune-related genes signature based on CXCL2, SEMA3G, PDGFD, and UCN is closely associated with the prognosis of renal clear cell carcinoma (Gao et al 2020). In this study, we identi ed that TIICs proportion is closely correlated with the prognosis of renal cancer, which was diffent from the previous study.…”
Section: Different Immune Clusters Are Associated With the Prognosis contrasting
confidence: 62%
“…We inferred that the decreased proportion of resting mast cells, which reflected the enhancement of activated mast cells activities, was associated with a poor prognosis due to the protumorigenic effects of activated mast cells. In addition, a previous study showed a four immune-related genes signature based on CXCL2, SEMA3G, PDGFD, and UCN is closely associated with the prognosis of renal clear cell carcinoma [ 52 ]. In this study, we identified that TIICs proportion is closely correlated with the prognosis of renal cancer, which was diffent from the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…K‐M analysis and ROC curve were performed in the ICGC database by using the R package. To further verify the prognostic capabilities of the signature, we calculated and compared the C‐index in both TCGA and ICGC database 19 …”
Section: Methodsmentioning
confidence: 99%
“…To further verify the prognostic capabilities of the signature, we calculated and compared the C-index in both TCGA and ICGC database. 19…”
Section: Validation Of the Immune-related Genebased Signaturementioning
confidence: 99%